Utilization of the Samudra Raksa Museum as A Learning Resource for Nusantara Maritime History from the 8th to the 16th Century - Dasri, Winarti; Wijayanti, Finna; Yuliantri, Rhoma Dwi Aria (Ridwan Institute, 2026)
The Samudra Raksa Museum is an important representation of the archipelago's maritime history that developed from the 8th to the 16th centuries AD. However, its utilization as a learning resource for history remains relatively minimal, especially in contextual learning oriented toward direct experience. This research aims to explore the potential of the Samudra Raksa Museum as an effective and relevant learning resource for history among students. A descriptive qualitative approach was used, with data collection techniques comprising observation, interviews, documentation, and literature studies. The results show that the Samudra Raksa Museum has high educational value through its collections and visual narratives, which represent the glory of shipping, trade, and maritime diplomacy of the archipelago's kingdoms—especially the Sriwijaya Kingdom. This study recommends integrating museum visits into the national history curriculum. In conclusion, the Samudra Raksa Museum serves as a highly effective and interactive learning resource that enriches maritime history education. To optimize its use, it is recommended to integrate museum visits into the national history curriculum, develop structured learning modules, enhance teacher preparedness, and expand accessibility through digital platforms such as virtual tours. Collaboration between schools and museums, along with logistical support, is essential to ensure equitable and contextual learning experiences for all students.